Implications of WRF model resolutions on resolving rainfall variability with topography over East Africa - Mwanthi, Anthony M.; Mutemi, Joseph N.; Opijah, Franklin J.; Mutua, Francis M.; Atheru, Zachary; Artan, Guleid (Frontiers in Climate, 2024)
Rainfall is the major resource that supports most livelihoods in East Africa. Most disasters in the region also can be traced to hydrometeorological processes. There is a dire need to improve the accuracy of forecast information across all timescales for life-saving applications related with to extreme weather such as floods, heat stress, and droughts, and in support of key economic activities in agriculture, tourism, and energy sectors. The complex topography in the region defined by sharp gradients in elevation, many inland water bodies, and land cover conversions, forms a case where mesoscale processes are dominant. The sparse station network, however, limits the proper understanding of such limited area drivers of weather variability and limits the proper calibration of satellite rainfall estimates. We apply the Weather Research and Forecasting (WRF) model at a convection-permitting scale forced by the National Centers for Environmental Prediction (NCEP) -Global Data Assimilation System (GDAS) Global Forecast System (GFS) final (FNL) reanalysis to simulate weather patterns over East Africa over the period 3 rd to 30 th April 2018. Comparing coarse and high-resolution model outputs affirms that the choice of model resolution is critical in capturing the topographical influence of weather over East Africa. Although the coarse resolution setup reasonably simulated rainfall over large mountains, only the convection-permitting configuration could accurately resolve weather process over contrasting topographical features. Ultimately, adoption of high-resolution modeling systems is critical for improving the quality of operational forecasts.MA designed and conducted the research under supervision of MJ, FO, FM. MA drafted the manuscript which was reviewed and edited by all co-authors. ZA and GA sourced the funding to cater for publishing chargers.